Трансформація гідроксильних протонів в процесі створення водно-спиртових сумішей - Кузьмін, Олег Володимирович; Мирончук, Валерій Григорович; Топольник, Віра Григорівна (My University, 2014)
Експериментально доведена залежність швидкості і характеру встановлення термодинамічної рівноваги, а також отримання оптимальних органолептичних характеристик водно-спиртових сумішей залежно від способу водопідготовки і часу контакту компонентів. Методи: 1Н ЯМР спектроскопія водно-спиртових сумішей, методи оцінки фізико-хімічних та органолептичних показників води, етанолу, водно-спиртових сумішей. The aim of this work is the investigation of transformation mechanisms of hydrogen bonds nets of ethanol and water in the process of making aqueous alcoholic mixtures. Methods: 1Н NMR spectroscopy of aqueous alcoholic mixtures, evaluation methods of physicochemical and organoleptic characteristics of water, ethanol, aqueous alcoholic mixtures. Results: experimental evidence depending speed and nature of thermodynamic equilibrium, and optimum organoleptic characteristics aqueous alcoholic mixtures according to the method of water treatment and contact time components. Scientific novelty: based on this study identified fundamental difference in the behavior of the aqueous alcoholic mixtures received alcohol and water, held various treatments. Practical value: we obtained the system steady and unsteady balance hydroxyl protons in aqueous alcoholic mixtures, which are different in the organoleptic properties.
Keywords: кафедра технологічного обладнання та комп’ютерних технологій проектування; кафедра технології ресторанної і аюрведичної продукції; горілка; етанол; вода; водно-спиртові суміші; 1H ЯМР спектроскопія; гідроксильні протони; vodka; ethanol; water; aqueous alcoholic mixtures; 1H NMR spectroscopy; hydroxyl protons